A Community-Based Health Education Intervention on Adolescents’ Knowledge and Attitudes Toward Sexual Violence Prevention - Sukmawati Sukmawati; Lilis Mamuroh; Furkon Nurhakim (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background: Adolescents are vulnerable to sexual violence, which adversely affects their physical, psychological, and social well-being, as well as their development. Community-based health education is a key strategy for improving knowledge and attitudes.Aims: This study aimed to evaluate the effectiveness of a community-based health education intervention in enhancing adolescents’ knowledge and attitudes toward sexual violence prevention.Methods: A quasi-experimental study with a one-group pretest–posttest design was conducted among 132 adolescents selected through purposive sampling in Jatinangor District, Sumedang Regency, in February 2026. Data were collected using validated questionnaires to assess knowledge and attitudes. The intervention comprised lectures, interactive discussions, video-based learning, and role-plays, delivered in three 60-minute sessions, once per week over a three-week period. Data were analyzed using frequency distributions and the Wilcoxon signed-rank test.